The 2012 Greek retrofit and borrowing costs in the European periphery - Mitu Gulati; Patrick Bolton; Ugo Panizza; Xuewen Fu (Graduate Institute of International and Development Studies, 2023)
This article examines the impact of Greece retroactively, via legislation, changing the terms in hundreds of billions of euros worth of Greek government bonds governed by domestic Greek law. As the abrogation of gold clauses in US government bonds by the US Congress in 1933 had been, the Greek action was decried as violative of the rule of law and sure to negatively impact the future ability of Euro area sovereigns to borrow. We test whether the Greek action had negative spillovers on European government debt markets. We find no evidence of increased borrowing for even the most peripheral European economies from the Greek action.
Keywords: 330